Community preparedness in ecotourism development and their role in maintaining the natural resources in Kadamaian area, Sabah - Chong, Franey Joseph; Le, Gao; Abdul Aziz, Nor Akmar; Pengiran Bagul, Awangku Hassanal Bahar Pengiran Bagul; Saikim, Fiffy Hanisdah (Journal of Tropical Biology & Conservation (JTBC), 2021)
Community preparedness in ecotourism development and their role in maintaining natural resources is necessary. Yet, many examples throughout the world suggest that local communities are unable to participate in development of ecotourism and maintaining natural resources. A preliminary study was carried out to identify the preparedness of local communities in ecotourism, as well as to determine the Strength, Weakness, Opportunities, and Threat (SWOT) that effect the preparedness of local communities. Sociological interviews was a recommend networking as the determining the factor. This paper aims to assess the potential of ecotourism in the Kadamaian area and the preparedness in development of ecotourism by the local community. We focused on evaluating the relationship between environment impact and ecotourism by the local community in terms of sustainable tourism development, which can provide an insight in future management for government, stakeholders and managers. This preliminary study shows that local communities are highly prepared in ecotourism development and inmaintaining natural resources, and the result could assist them in conserving natural resources.